Serum globulin and albumin to globulin ratio as potential diagnostic biomarkers for periprosthetic joint infection: a retrospective review - Ye, Yongyu; Chen, Weishen; Gu, Minghui; Xian, Guoyan; Pan, Baiqi; Zheng, Linli; Zhang, Ziji; Sheng, Puyi (Journal of orthopaedic surgery and research, 2020)
Background Periprosthetic joint infection (PJI) has been increasingly documented; however, its preoperative accurate diagnosis remains challenging. Furthermore, there is a dire need to identify appropriate and effective biomarkers. We aimed to evaluate the relationship between globulin, albumin to globulin (A/G) ratio, and development of PJI in patients undergoing revision total joint arthroplasty (TJA). Methods A retrospective study was conducted on patients who had undergone revision TJA between 2011 and 2018 (89 with aseptic mechanic failure and 38 with PJI). The serum proteins were explored using univariate analysis followed by multivariate logistic regression. The diagnostic performance of these proteins was assessed by the receiver operating characteristic (ROC) curve. Results Higher globulin levels (odds ratio [OR], 1.239; P < 0.001) and lower A/G ratio (OR, 0.007; P < 0.001) were strongly associated with the risk of PJI. ROC curve analysis demonstrated reasonable diagnostic performance for globulin (area under the curve [AUC], 0.77; sensitivity, 78.95%; and specificity, 69.66%) and A/G ratio (AUC, 0.779; sensitivity, 65.79%; and specificity, 78.65%). Conclusions Both globulin and A/G ratio were associated with PJI and may serve as potential adjuvant biomarkers in the diagnosis of PJI. Keywords: Periprosthetic joint infection, Globulin, Albumin to globulin ratio, Diagnosis